Estrategia didáctica apoyada en las tecnologías de la información y la comunicación para mejorar la comprensión auditiva del idioma inglés de los estudiantes de décimo año de educación básica sección diurna en el colegio técnico agropecuario Río Nangaritza cantón Nangaritza, provincia de Zamora Chinchipe, año lectivo 2012-2013 - Zhiñín Quezada, Lidia Viviana (2015)
The Ministry of Education of Ecuador, lists English as the main communication tool in the world, and thus encourages support of this area of study. Based on the urgent need to improve English language teaching, the idea of research in the Educational Unit Rio Nangaritza in Canton Nangaritza, Zamora Chinchipe was developed to study one of the most important skills in learning a foreign language, according to many authors: English language listening. The treatment of this problem consisted of an investigation that was applied scientific reservation as well as a survey based on a questionnaire given to students and observation guides given to teachers of Tenth Year of Basic Education. This work demonstrated that the teacher uses limited technological resources in the teaching and learning process to develop listening comprehension and it is only CD, and sometimes the teacher reads the text. It was verified through the test that students have a very low level in listening skills. Consequently, the low students’ interest increases to learn English language. Therefore, taking into consideration the results and after reviewing to, It can be stated that this research work is based on the application of communicative approach to foreign language acquisition and Vigosyky’s socio cultural theory for the implementation of group activities and pair work, interaction activities which strengthen the development of listening comprehension of English. Noticed the necessity of alternative solutions in the development of the listening skill, it was necessary to design and implement a teaching strategy supported with the Information Technology and Communication in order to motivate and improve English listening comprehension. It is expressively mentioned the positive contribution of the students in the implementation of the teaching strategy, due to active participation and the level of this skill improved dramatically. Finally it can be stated that this alternative could be employed with other levels of learning.